Effect of Repeated Administration of ɣ-Valerolactone (GVL) and GHB in the Mouse: Neuroadaptive Changes of the GHB and GABAergic System - Paolo Frisoni; Giorgia Corli; Sabrine Bilel; Micaela Tirri; Laura Camilla Gasparini; Letizia Alfieri; Margherita Neri; Fabio De-Giorgio; Matteo Marti (Pharmaceuticals, 2023)
Background: Gamma-hydroxybutyric acid (GHB) at low dosages has anxiolytic effects and promotes REM sleep and low-wave deep sleep. In the U.S., the legal form of GHB is prescribed to adults suffering from narcolepsy-associated cataplexy; the sodium salt of GHB is reserved for alcohol-addiction treatment. GHB is also a molecule of abuse and recreational use, it is a controlled substance in several countries, so gamma-valerolactone (GVL) has frequently been used as a legal substitute for it. GHB’s abuse profile is most likely attributable to its anxiolytic, hypnotic, and euphoric properties, as well as its widespread availability and inexpensive/low cost on the illicit market. Methods: Our study is focused on evaluating the potential effects on the mouse brain after repeated/prolonged administration of GHB and GVL at a pharmacologically active dose (100 mg/kg) through behavioral study and immunohistochemical analysis using the markers tetraspanin 17 (TSPAN17), aldehyde dehydrogenase 5 (ALDH5A1), Gamma-aminobutyric acid type A receptor (GABA-A), and Gamma-aminobutyric acid type B receptor (GABA-B). Results: Our findings revealed that prolonged administration of GHB and GVL at a pharmacologically active dose (100 mg/kg) can have effects on a component of the mouse brain, the intensity of which can be assessed using immunohistochemistry. The findings revealed that long-term GHB administration causes a significant plastic alteration of the GHB signaling system, with downregulation of the putative binding site (TSPAN17) and overexpression of ALDH5A1, especially in hippocampal neurons. Our findings further revealed that GABA-A and GABA-B receptors are downregulated in these brain locations, resulting in a greater decrease in GABA-B expression. Conclusions: The goal of this study, from the point of view of forensic pathology, is to provide a new methodological strategy for better understanding the properties of this controversial substance, which could help us better grasp the unknown mechanism underlying its abuse profile.